2018
DOI: 10.2147/ndt.s183436
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different frequencies of electroacupuncture on BDNF and NGF expression in the hippocampal CA3 area of the ischemic hemisphere in cerebral ischemic rats

Abstract: ObjectiveThe aim of this study was to observe the effects of different frequencies of electroacupuncture (EA) on expression of brain-derived neurotrophic factor (BDNF) and nerve growth factor (NGF) in the hippocampal CA3 region of cerebral ischemic rats.MethodsMiddle cerebral artery occlusion was successfully introduced to simulate cerebral infarction in 48 healthy male Sprague–Dawley rats. Totally, 48 rats were randomly divided into three groups: the control group, the EA 5-Hz group, and the EA 50-Hz group, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
(28 reference statements)
1
1
0
Order By: Relevance
“…This result appears to be in agreement with recent papers showing that EA ameliorates cognitive impairment through inhibition of Ca 2+mediated neurotoxicity in a rat model of cerebral ischemiareperfusion injury [54]. We also observed the effect of EA on the improvement of learning and memory ability in MCAO/R rats, which may be related to the stimulation of the brain by EA to produce endogenous NGF [55]. Other recent studies have demonstrated that it is feasible to attenuate cognitive impairment by reducing hippocampal neuronal degeneration and apoptosis [56].…”
Section: Discussionsupporting
confidence: 93%
“…This result appears to be in agreement with recent papers showing that EA ameliorates cognitive impairment through inhibition of Ca 2+mediated neurotoxicity in a rat model of cerebral ischemiareperfusion injury [54]. We also observed the effect of EA on the improvement of learning and memory ability in MCAO/R rats, which may be related to the stimulation of the brain by EA to produce endogenous NGF [55]. Other recent studies have demonstrated that it is feasible to attenuate cognitive impairment by reducing hippocampal neuronal degeneration and apoptosis [56].…”
Section: Discussionsupporting
confidence: 93%
“…Different frequencies of electroacupuncture could produce different effects. For neurological reconstruction, electroacupuncture could promote the expression of NGF and BDNF in the hippocampal CA3 region of cerebral ischemic rats, and the 50-Hz electroacupuncture effect was more obvious [ 32 ]. For cerebral blood flow, the electroacupuncture in both 2 and 15 Hz groups induced the increase of cerebral blood flow in rats [ 33 ].…”
Section: Discussionmentioning
confidence: 99%